Manajemen Konflik untuk Mewujudkan Lingkungan Belajar yang Positif di Sekolah Dasar - Erina Kartika Sulistiana; Devina Novita Anggi; Iza Hasna Nasywa; Lisa Virdinarti Putra (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
Conflict management in Elementary Schools (SD) is a crucial aspect in creating a safe, comfortable learning environment that supports students' social and academic development. Conflicts that occur between students, teachers, and parents can have a negative impact on the school climate, disrupt the learning process, and affect relationships between individuals in the educational environment. This article aims to describe the importance of conflict management in elementary schools, by reviewing the types of conflict, causes, and strategies that can be applied. This study uses a literature study method with a descriptive qualitative approach, based on theoretical studies and previous research results. The results of the study indicate that conflicts in schools can be classified into conflicts between individuals, between groups, and between organizations, which are triggered by various factors such as uncontrolled emotions, differences in character, and ineffective communication. To overcome this, a comprehensive conflict management strategy is needed such as a mediation approach, the application of positive discipline, and the integration of social-emotional learning (SEL). In conclusion, the active involvement of teachers and the creation of an inclusive school environment are very important in preventing and handling conflict constructively, so that it can support the creation of a harmonious and productive learning atmosphere.